Running and Other Stories - Xaba, Makhosazana (Book collections on Project MUSE., 2013)
Turning her back on what is considered conventional, Makhosazana Xaba engages with her subject-matter on a revolutionary level in Running and Other Stories. She takes tradition--be that literary tradition, cultural tradition, gender tradition--and re-imagines it in a way that is liberating and innovative. Bracketed by Xaba's revisitings of Can Themba's influential short story, The Suit, the ten stories in this collection, while strongly independent, are in conversation with one another, resulting in a collection that can be devoured all at once or savoured slowly, story by story. By re-envisioning the ordinary and accepted, Xaba is creating a space in which women's voices are given a rebirth.